2017
DOI: 10.4172/2157-7595.1000280
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Health Utility of Patients after Cardiac Surgery

Abstract: Background: Health utility, which can be assessed by several preference-based utility measures, is an important measure in the analysis of cost effectiveness in health care. We aimed to examine differences in health utility by age following recovery phase II cardiac rehabilitation (CR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In addition, we previously reported that no age-related differences in health utility were found between middle-aged and older patients upon entrance into a phase II CR program at 1 month and at 3 months after cardiac surgery [21]. This indicates that aging might not reflect differences in the average SF-6D utility scores of patients at 5 months after cardiac surgery, and these findings might support those of the previous study [21].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In addition, we previously reported that no age-related differences in health utility were found between middle-aged and older patients upon entrance into a phase II CR program at 1 month and at 3 months after cardiac surgery [21]. This indicates that aging might not reflect differences in the average SF-6D utility scores of patients at 5 months after cardiac surgery, and these findings might support those of the previous study [21].…”
Section: Discussionsupporting
confidence: 79%
“…However, a recent study reported that although their results did not differ significantly based on age, sex, emergent status, or history of heart failure or arrhythmias, participation in CR was of more benefit to the patients who underwent cardiac surgery [29]. In addition, we previously reported that no age-related differences in health utility were found between middle-aged and older patients upon entrance into a phase II CR program at 1 month and at 3 months after cardiac surgery [21]. This indicates that aging might not reflect differences in the average SF-6D utility scores of patients at 5 months after cardiac surgery, and these findings might support those of the previous study [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations